34.3k views
5 votes
Simplify: 5x-(2x+y)


help

2 Answers

4 votes

Answer:

Simplifying

5x(2x + y) = 0

(2x * 5x + y * 5x) = 0

Reorder the terms:

(5xy + 10x2) = 0

(5xy + 10x2) = 0

Solving

5xy + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '5x'.

5x(y + 2x) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'x' equal to zero and attempt to solve:

Simplifying

x = 0

Solving

x = 0

Move all terms containing x to the left, all other terms to the right.

Simplifying

x = 0

Subproblem 2

Set the factor '(y + 2x)' equal to zero and attempt to solve:

Simplifying

y + 2x = 0

Reorder the terms:

2x + y = 0

Solving

2x + y = 0

Move all terms containing x to the left, all other terms to the right.

Add '-1y' to each side of the equation.

2x + y + -1y = 0 + -1y

Combine like terms: y + -1y = 0

2x + 0 = 0 + -1y

2x = 0 + -1y

Remove the zero:

2x = -1y

Divide each side by '2'.

x = -0.5y

Simplifying

x = -0.5y

Solution

x = {0, -0.5y}

User Alek
by
5.7k points
4 votes

Answer:

3x-y

Explanation:

User PavlinII
by
5.0k points